2021
DOI: 10.1097/jxx.0000000000000660
|View full text |Cite|
|
Sign up to set email alerts
|

The level of quality care nurse practitioners provide compared with their physician colleagues in the primary care setting: A systematic review

Abstract: Background: There is an increasing demand for high-quality primary care providers without adequate supply to meet the need. Nurse practitioners (NPs) are uniquely positioned to fill this demand but influence on regulatory practice authority from concerned groups regarding patient safety and quality of care has delayed this as an effective solution.Objectives: The objective was to address concerns abovt NP-led care by examining evidence regarding patient safety, clinical outcomes, cost, and patient satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Otro estudio demostró que no existían diferencias entre un diagnóstico emitido entre una enfermera y un médico cuando se trataba de enfermedades agudas leves 16 . Una de las revisiones sistemáticas más recientes 17 concluye que la calidad de la atención al paciente proporcionada por las enfermeras en el ámbito de la atención primaria es igual o superior, a la de los médicos.…”
Section: Discussionunclassified
“…Otro estudio demostró que no existían diferencias entre un diagnóstico emitido entre una enfermera y un médico cuando se trataba de enfermedades agudas leves 16 . Una de las revisiones sistemáticas más recientes 17 concluye que la calidad de la atención al paciente proporcionada por las enfermeras en el ámbito de la atención primaria es igual o superior, a la de los médicos.…”
Section: Discussionunclassified
“…One study that confirmed comparable care quality between NPs and physicians also found that hospitals with NPs who complied with guidelines for treating ICU patients with septic shock had lower mortality rates [ 7 ]. In addition, a systematic review noted that in the primary care setting, NPs provide care that is not only equal to that of physicians but in some cases is superior [ 8 ]. For example, NPs are associated with higher patient satisfaction.…”
Section: Scope and Valuementioning
confidence: 99%
“…The FPA steering committee was comprised of APRN leadership, a physician executive sponsor, operational champions, representatives from public affairs/marketing, human resources, risk, compliance, credentialing practitioner verifi cation department, provider contracting, and leaders from hospital medical staff offi ces. The goal of the FPA steering committee included: (1) defi ning the current state including numbers of potential APRNs qualifying for FPA and departments that would be affected by the change; (2) defi ning workfl ows and processes for all departments affected by the change; (3) clarifying relationships between APRNs with FPA and their physician consultants, including reenvisioning the requirements for WCA; (4) creating a pathway identifying and encouraging those APRNs who qualify to apply; (5) developing and providing encouraging and consistent messaging to APRNs, physicians, and other key stakeholders via a communication plan to acculturate the concept and garner support for change; and (6) identifying and amending internal policies that would be affected by these sweeping changes.…”
Section: ■ Multidisciplinary Steering Committeementioning
confidence: 99%